The Influence of Management Accounting Information, Performance Measurement System, and Reward System On Managerial Performance In Modern Retail Companies In Cirebon City - Mulyatno, Roni; Mulyasari Dewi, Rahmawati; Rismawati, Rismawati; Nur Warsya, Riqzma (The Islamic Education and Multiculturalism Foundation, 2024)
This study aims to determine the effect of the application of accounting information, performance measurement systems and reward systems to managerial performance in modern retail companies in Cirebon City. The number of samples used in this study amounted to 76 people. The research sample consisted of lowerlevel managers (lower management) to top (top management). The results showed that the application of management accounting information had an effect on managerial performance, the performance measurement system had no effect on managerial performance, and the reward system had a significant effect on employee performance, while simultaneously significantly affected the performance of modern retail companies in Cirebon